2019
DOI: 10.3390/su11071995
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in the Chemical Composition of Biofertilizers, Potential Agronomic Use, and Heavy Metal Contents of Different Agro-Industrial Wastes

Abstract: Several agro-industrial, livestock, and food wastes can be recycled to create biofertilizers. This diversity of raw materials can result in nutritional imbalance and an increase in heavy metal content, which could make the final product unfeasible. Thus, the chemical characterization of the raw materials and their influence on the sustainable and safe production of biofertilizers need to be better understood. In this context, the objective of the present study was to evaluate the chemical characteristics of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…For the purpose of understanding the relationship between input variables, parameters and the predictive proficiency of the MONICA model, a comprehensive sensitivity analysis was conducted using an improved Morris elementary effects screening method (Fig. C1; Morris, 1991;Campolongo et al, 2007;Pujol, 2009). The algorithm demonstrates the capability to determine the importance of parameters in relatively short computing times (Campolongo et al, 2007;Confalonieri et al, 2010).…”
Section: Screening Of Variables Relevant To Soil Carbon Turnovermentioning
confidence: 99%
“…For the purpose of understanding the relationship between input variables, parameters and the predictive proficiency of the MONICA model, a comprehensive sensitivity analysis was conducted using an improved Morris elementary effects screening method (Fig. C1; Morris, 1991;Campolongo et al, 2007;Pujol, 2009). The algorithm demonstrates the capability to determine the importance of parameters in relatively short computing times (Campolongo et al, 2007;Confalonieri et al, 2010).…”
Section: Screening Of Variables Relevant To Soil Carbon Turnovermentioning
confidence: 99%
“…This increase usually occurs up to 700 °C, at which P losses start due to volatilization [14]. Compared with biochar from multiple feedstocks [19] and with other types of soil amendments [20], SSB has higher P levels, with great potential for use as a P fertilizer. Increases of Ca, Mg, S and micronutrients levels have also been reported in previous studies with SSB at 300ºC [8,17,21].…”
Section: Physical and Chemical Characteristicsmentioning
confidence: 99%
“…The amount of N, P, and K is nearly 0.45, 0.81 and 2.93 g kg −1 in biofertilizers. Rice‐husk ash, CC, and PSA contain a small amount of calcium, potassium, magnesium, etc., and eggshell powder also contains calcium, which could be an alternative source of the minerals in biofertilizers 125. Omatola and Onojah126 concluded that agricultural wastes such as rice husk can be used as chemical fertilizers, insecticides, pesticides, and so forth.…”
Section: Direct Utilization Of Agro‐wastesmentioning
confidence: 99%